Основные принципы концепции всеобщего управления энергосбережением (Путеводитель предпринимателя)
Basic principles of the concept of universal energy saving control The essence of the basic principles and concepts of universal energy efficiency management. The necessity of taking into account the recommendations of the International Energy Agency in determining the focus of strategic management of energy conservation.